Evidence-based scientific exercise guidelines for adults with spinal cord injury: an update and a new guideline. Issue 4 (April 2018) - Martin Ginis, Kathleen; van der Scheer, Jan; Latimer-Cheung, Amy; Barrow, Andy; Bourne, Chris; Carruthers, Peter; Bernardi, Marco; Ditor, David; Gaudet, Sonja; de Groot, Sonja; Hayes, Keith; Hicks, Audrey; et al.
Abstract Objectives To describe the process and outcomes of using a new evidence base to develop scientific guidelines that specify the type and minimum dose of exercise necessary to improve fitness and cardiometabolic health in adults with spinal cord injury (SCI). Setting International. Methods Using Appraisal of Guidelines, Research and Evaluation (AGREE) II reporting criteria, steps included (a) determining the guidelines' scope; (b) conducting a systematic review of relevant literature; (c) holding three consensus panel meetings (European, Canadian and International) to formulate the guidelines; (d) obtaining stakeholder feedback; and (e) process evaluation by an AGREE II consultant. Stakeholders were actively involved in steps (c) and (d). Results For cardiorespiratory fitness and muscle strength benefits, adults with a SCI should engage in at least 20 min of moderate to vigorous intensity aerobic exercise 2 times per week AND 3 sets of strength exercises for each major functioning muscle group, at a moderate to vigorous intensity, 2 times per week (strong recommendation). For cardiometabolic health benefits, adults with a SCI are suggested to engage in at least 30 min of moderate to vigorous intensity aerobic exercise 3 times per week (conditional recommendation). Conclusions Through a systematic, rigorous, and participatory process involving international scientists and stakeholders, a new exercise guideline was formulated for cardiometabolic health benefits. A previously published SCI guideline was endorsed for achieving fitness benefits. These guidelines represent an important step toward international harmonization of exercise guidelines for adults with SCI, and a foundation for developing exercise policies and programs for people with SCI around the world.